"Help Me to Improve my Own Priorities!": A Feasibility Study of an Individualized Intensive Goal Training for Adolescents with Cerebral Palsy. (21st September 2021) - Feitosa, Aline M.; Mancini, Marisa C.; Silvério, Ana Paula M.; Gordon, Andrew M.; Brandão, Marina B.
Abstract: Aim: To investigate the feasibility and the preliminary effects of an individualized intensive goal training for adolescents with cerebral palsy (CP). Methods: Twelve adolescents with CP (12–17 years old, MACS II-III, GMFCS I-IV) identified functional goals to be practiced three hours/day, five days/week, for two weeks. The feasibility aspects included the participant's adherence (i.e., daily logs), the adequacy of the instruments used, and the participant's satisfaction with the intervention (i.e., structured questionnaire). Outcome measures included the Canadian Occupational Performance Measure (COPM), Pediatric Evaluation of Disability Inventory (PEDI) (self-care; mobility), Children Helping Out: Responsibilities, Expectations and Supports (CHORES), Participation and Environment Measure-Children and Youth (PEM-CY) (home) and Box and Blocks Test (BBT). Assessments were conducted one month and two days before the intervention, immediately and three months after the intervention. Friedman tests were used to test time-related differences in the outcome measures. Results: All adolescents completed and reported satisfaction with the proposed intervention. Significant improvements were observed in performance and satisfaction (COPM), in functional skills and caregiver assistance in self-care and in the performance of household tasks. There were no significant differences in mobility skills, independence in mobility or household tasks, home participation, or manual dexterity. Conclusion: The intensive training was feasible and promoted improvements in functional goals and daily functioning of adolescents with CP.